Screening of Stat3 inhibitory effects of Korean herbal medicines in the A549 human lung cancer cell line - Jong-Shik Park; Ok-Sun Bang; Jinhee Kim (Integrative Medicine Research)
Background: The transcription factor signal transducer and activator of transcription 3 (Stat3) is constitutively activated in many human cancers. It promotes tumor cell proliferation, inhibits apoptosis, induces angiogenesis and metastasis, and suppresses antitumor host immune responses. Therefore, Stat3 has emerged as a promising molecular target for cancer therapies. In this study, we evaluated the Stat3-suppressive activity of 38 herbal medicines traditionally used in Korea. Methods: Medicinal herb extracts in 70% ethanol were screened for their ability to suppress Stat3 in the A549 human lung cancer cell line. A Stat3-responsive reporter assay system was used to detect intracellular Stat3 activity in extract-treated cells, and Western blot analyses were performed to measure the expression profiles of Stat3-regulated proteins. Results: Fifty percent of the 38 extracts possessed at least mild Stat3-suppressive activities (i.e., activity less than 75% of the vehicle control). Ethanol extracts of Bupleurum falcatum L., Taraxacum officinale Weber, Solanum nigrum L., Ulmus macrocarpa Hance, Euonymus alatus Sieb., Artemisia capillaris Thunb., and Saururus chinensis (Lour.) Baill inhibited up to 75% of the vehicle control Stat3 activity level. A549 cells treated with these extracts also had reduced Bcl-xL, Survivin, c-Myc, and Mcl-1 expression. Conclusion: Many medicinal herbs traditionally used in Korea contain Stat3 activity-suppressing substances. Because of the therapeutic impact of Stat3 inhibition, these results could be useful when developing novel cancer therapeutics from medicinal herbs.